A motivational interviewing intervention improves the burden of physical symptoms in patients with heart failure: A secondary outcome analysis of a randomized clinical trial. (29th July 2021) - Caggianelli, G; Iovino, P; Rebora, P; Occhino, G; Zeffiro, V; Locatelli, G; Ausili, D; Alvaro, R; Riegel, B; Vellone, E
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Center of Excellence for Nursing Scholarship, Rome, Italy Background. Patients with heart failure (HF) experience a variety of physical symptoms. Symptoms are perceived by patients as burdensome and, as such, negatively affect  quality of life. Besides, physical symptoms are among the first reasons for seeking emergency care and hospitalization. Findings from the MOTIVATE-HF trial show that motivational interviewing (MI) leads to better self-care. However, whether MI also reduces the burden of physical symptoms is not yet known. Purpose. To evaluate the effectiveness of MI on the burden of physical symptoms in patients with HF. Methods. Secondary outcome analysis of the MOTIVATE-HF trial. The study was a three-arm, multicenter randomized controlled trial with a 12-month follow-up. Patients with HF and their informal caregivers were enrolled and randomly divided into three arms: MI performed only with patients (Arm 1); MI performed both with patients and caregivers (Arm 2); usual care (Arm 3). Patients with a diagnosis of HF in NYHA functional class II-IV were recruited in three Italian centers. Participants underwent one face-to-face MI session, followed by three phone calls within two months from enrollment. Physical symptoms were measured with the Heart Failure Somatic Perception Scale (HFSPS) with the dimensions of dyspnea, chest discomfort, early and subtle, and edema. Higher scores at the HFSPS and its dimensions indicate worse physical symptom. Data were collected at baseline, and 3 (T1), 6 (T2), 9 (T3) and 12 (T4) months after enrollment. T-test was used to compare differences in HFSPS scores in Arms 1 and 2 versus Arm 3 at each follow-up. Changes over time were analyzed with mixed linear longitudinal models. Results. A sample of 510 patients (median 74 years, 58% male) and their caregivers (median 55 years, 75.5% female) were randomized to Arm 1 (n = 155), Arm 2 (n = 177) and Arm 3 (n = 178). Chest discomfort improved in Arms 1 and 2 versus Arm 3 at T4 (mean difference(Δ): -8.13, P = .014). Dyspnea also improved in Arms 1 and 2 than Arm 3 both at T3 and T4 (Δ: -7, P = .027 and Δ: -6.78, P = .038, respectively). HFSPS total score improved in Arms 1 and 2 versus Arm 3 at T3 (Δ: -4.55, P = .048). Over the year of observation, the mixed linear longitudinal models showed a significant improvement in Chest discomfort and total HFSPS score in Arm 2 versus Arm 3 (β = -2.61, P = .002 and, β = -1.35, P = .02). Conclusions. The results of this secondary analysis indicate that MI may be effective in decreasing the burden of physical symptoms in HF patients, especially if also caregivers are involved in the intervention. Since symptom burden is among the first reasons for seeking emergency care and hospitalization in HF, MI might be a viable option to improve symptom burden via self-care.